Harnessing education and lifestyle change to support transitional health for returning citizens: a feasibility study protocol - Rodlescia S. Sneed; Leon El-Alamin; Marsha Thrower; Jessica Nadrowski; Kayla Habermehl (Pilot and Feasibility Studies, 2023)
Abstract Background Exercise and healthy eating are known to reduce chronic disease risk; however, formerly incarcerated individuals (i.e., returning citizens) face significant social barriers when attempting to engage with existing community-based physical activity and nutrition programs. Given the high disease burden and unique educational needs of returning citizens, this proposed work fills an important gap in the support services currently offered to this population. Methods This article describes a process for evaluating the feasibility and acceptability of a physical activity and nutrition intervention tailored to the needs of returning citizens via a partnership between an academic research organization and a community-based reentry program for returning citizens. Staff from the community-based reentry program will train four returning citizens as group fitness instructors and work with a nutritionist to design a 16-week nutrition education curriculum. Reentry program staff will enroll up to 15 formerly incarcerated adults (aged 18 +) in the exercise and nutrition program. Participants will take part in weekly nutrition classes led by the nutritionist and weekly group exercise classes led by a peer instructor. Research staff will evaluate program success in four domains: reach, preliminary effectiveness, implementation, and maintenance. Results This feasibility study will allow us to design and test a program that can eventually be evaluated in a large, randomized trial. It also addresses the multitude of social determinants that impact the health of returning citizens and builds a framework for program sustainability. Individuals recruited as fitness trainers will acquire skills and certifications that may be used to sustain physical fitness activities within the reentry program. Conclusions This feasibility study will test our ability to address social determinants that impact the health of returning citizens through a peer-led physical activity and nutrition programming. In the long term, study results may inform development and implementation of reentry programming and policy on a wider scale.